Cervical pessary for preterm twin pregnancy in women with a short cervix - Da Un Jung; Min Jung Choi; Sun Young Jung; Suk Young Kim (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveWe aimed to evaluate the effectiveness of cervical pessary for extending twin pregnancy in women with a short cervix.MethodsBetween January 2014 and March 2019, the use of a cervical pessary for twin pregnancy in women with a cervical length of ≤15 mm was investigated between 16 and 28 weeks of gestation. We included women with a shortened cervix after a cerclage procedure and visible fetal membranes and cervical dilatation. Thirteen patients underwent pessary insertion and were matched with a control group of 15 patients. Pregnancy and neonatal outcomes were compared between the groups. We excluded women with major fetal anomalies discovered before or after birth and known placenta previa.ResultsWomen who underwent pessary insertion were diagnosed with a short cervix (0.65±0.47 vs. 0.66±0.51 cm in the pessary and control groups, respectively; P=0.957) at a gestational age similar to that of the controls (23.29 vs. 25.14 weeks, P=0.294). There was no significant difference in gestational age at delivery between them (33.29 vs. 27.29 weeks in the pessary and control groups, respectively, P=0.058). The pessary group had a longer interval between the diagnosis and delivery than the control group (60.7±28.3 vs. 22.6±24.5 days, P=0.001). The number of adverse neonatal outcomes was significantly lower in the pessary group (n=7; 28.0%) than in the control group (n=14; 58.3%; P=0.032).ConclusionThe use of a cervical pessary may prolong gestation in twin pregnancies in women with an extremely short cervix until viable gestational age.